Predictors of seropositivity to SARS-CoV-2 among employees at a large urban medical center - Kupferwasser, Deborah; Flores, Evelyn A.; Merino, Prudencio; Tran, Donna Phan; Liu, Honghu; Huang, Yilan; Bolaris, Michael; Nguyen, Megan H.; Gonzales, Mildred; Da Silva, Wellington; Astorga-Cook, Leslie; Abueg, Angel; et al. (BMC public health, 2024)
Before SARS-CoV-2 vaccination availability, medical center employees were at high risk of COVID-19. However, risk factors for SARS-CoV-2 infection in medical center employees, both healthcare and non-healthcare workers, are poorly understood. From September-December 2020, free IgG antibody testing was offered to all employees at a large urban medical center. Participants were asked to complete a questionnaire on work and non-work related risk factors for COVID-19 infection. SARS-CoV-2 seropositivity was found in 4.7%. Seropositivity was associated with close contact with COVID-19 cases with or without the use of adequate personal protective equipment (PPE), (OR 3.1 [95% CI 1.4-6.9] and OR 4.7 [95% CI 2.0-11.0] respectively), never wearing a mask outside of work (OR 10.1 [95% CI 1.9-57]), and Native Hawaiian/Pacific Islander race (OR 6.3 95% CI (1.6-25)]. Among workers in a large urban medical center, SARS-CoV-2 seropositivity was associated with work-related COVID-19 close contacts and low mask use outside of work, suggesting that non-workplace close contacts are also relevant routes of COVID-19 spread among healthcare workers.